Web-Based Sustainability Disclosure Practices in Malaysian Public and Private Universities: Evidence from Content Analysis Approach - Nathasa Mazna Ramli; Agusdiwana Suarni (Invoice : Jurnal Ilmu Akuntansi, 2026)
Universities are increasingly expected to demonstrate transparency and accountability in addressing environmental and social challenges aligned with sustainable development. Web-based sustainability reporting has emerged as an important communication tool that allows higher education institutions to disclose sustainability initiatives and engage stakeholders effectively. This study aimed to examine the extent of sustainability information disclosed on university websites and to compare disclosure practices between public and private universities in Malaysia. A quantitative research design was employed using content analysis of official university websites. The population consisted of 20 public universities and 48 full private universities in Malaysia. Data were collected using a web-based sustainability reporting index consisting of 83 disclosure items across nine dimensions categorized into general, sustainability-specific, and university-specific aspects. The collected data were analyzed using descriptive statistics with SPSS, followed by independent sample t-tests and Mann–Whitney U tests to examine differences between institutional types. The findings indicated that Malaysian universities generally disclose sustainability information at a moderate level, with the highest disclosure found in general sustainability information (65%). Within sustainability-specific disclosures, the social dimension showed the highest level of reporting compared to economic and environmental aspects. The results also revealed that public universities demonstrate higher levels of sustainability disclosure than private universities across most dimensions. This study provides empirical evidence on the current state of digital sustainability disclosure in Malaysian higher education institutions. The findings contribute to the literature on sustainability reporting and offer practical insights for policymakers and university management in improving transparency, stakeholder communication, and institutional sustainability practices.